If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (m + -5)(5m + 3) = 0 Reorder the terms: (-5 + m)(5m + 3) = 0 Reorder the terms: (-5 + m)(3 + 5m) = 0 Multiply (-5 + m) * (3 + 5m) (-5(3 + 5m) + m(3 + 5m)) = 0 ((3 * -5 + 5m * -5) + m(3 + 5m)) = 0 ((-15 + -25m) + m(3 + 5m)) = 0 (-15 + -25m + (3 * m + 5m * m)) = 0 (-15 + -25m + (3m + 5m2)) = 0 Combine like terms: -25m + 3m = -22m (-15 + -22m + 5m2) = 0 Solving -15 + -22m + 5m2 = 0 Solving for variable 'm'. Factor a trinomial. (-3 + -5m)(5 + -1m) = 0Subproblem 1
Set the factor '(-3 + -5m)' equal to zero and attempt to solve: Simplifying -3 + -5m = 0 Solving -3 + -5m = 0 Move all terms containing m to the left, all other terms to the right. Add '3' to each side of the equation. -3 + 3 + -5m = 0 + 3 Combine like terms: -3 + 3 = 0 0 + -5m = 0 + 3 -5m = 0 + 3 Combine like terms: 0 + 3 = 3 -5m = 3 Divide each side by '-5'. m = -0.6 Simplifying m = -0.6Subproblem 2
Set the factor '(5 + -1m)' equal to zero and attempt to solve: Simplifying 5 + -1m = 0 Solving 5 + -1m = 0 Move all terms containing m to the left, all other terms to the right. Add '-5' to each side of the equation. 5 + -5 + -1m = 0 + -5 Combine like terms: 5 + -5 = 0 0 + -1m = 0 + -5 -1m = 0 + -5 Combine like terms: 0 + -5 = -5 -1m = -5 Divide each side by '-1'. m = 5 Simplifying m = 5Solution
m = {-0.6, 5}
| X^2-10x-3=-12 | | ln(y)=2x+5 | | (5x-3)+log(4)*(9-x)=3 | | (16x^2+36)= | | v=-3i | | (x-(0.21x))0.25=555.56 | | 0.1x-x=500 | | (x-(0.21x))0.25=500 | | 6r+7=22 | | 9x+7x-4x-5=55 | | xy+3x-7y-21=0 | | 3ax-11a=-3 | | 32r^2-112r+80=0 | | 2.5a+2b= | | 8x-6y=15 | | 500=((x-(0.21x))0.25)-0.1 | | 44x^2-39x+9=0 | | 39x^2-31x+6=0 | | (4b^2-4b)=0 | | 500=(x-(0.21x))0.25 | | (9b^2-81)=0 | | 4x-2(12x-x)=18 | | y^2-2x-6y+13=0 | | Sin(6x)*cos(6x)+1=0 | | Sin(6x)*cos(6x)-1=0 | | 8x-32=128-2x | | 8x-32=128+2x | | 8x-2x=128-32 | | 10x-x-2=-7 | | 10x-x-2=-7 | | T+10=11 | | 2w+2w-2+2w-2=68 |